VEHICLE DETECTION BY THE VARIOUS VEHICLE PARTS USING SVM TECHNIQUE - Priya, K Rathina; Ramachandiran, R. (IJRDO -Journal of Computer Science Engineering, 2015)
Traffic scrutiny is an essential topic in intelligent transportation systems. Vigorous vehicle detection and tracking is one difficult problem for complex urban traffic surveillance. As the traffic problems in urban areas are leaving to increase traffic surveillance systems based on record are involved over precedent decades. These systems are very much practical to observe and supervise various traffic situations such as traffic management, preclusion of calamity, also secure transportation. Vehicle detection has been the serious part of the traffic observation system for lots of years. However, vehicle detection method is at rest challenging discrepancy morphology ultimate side view is used to remove the vehicle routinely from the traffic image. This paper propose a rear-view automobile detection and tracking method based on multiple vehicle relevant parts using a still camera. We show that spatial modeling of these vehicle parts is decisive for overall performance.